Mechanical properties of sustainable concrete comprising various wastes - Ramy M. Reda; Hoda S. E. Mahmoud; Seleem S. E. Ahmad; Hossam El-Din M. Sallam (Scientific Reports, 2023)
Abstract Due to the rapid increase of pollution around the world, the disposal of waste materials such as granite powder (GP), iron powder (IP), brick powder (BP), and waste plastic particles (PP) is a major environmental problem in the entire world. Utilizing these industrial waste materials has many advantages for the construction industry regarding cost-effectiveness and the sustainability of natural resources. This investigation examined the addition of GP, IP, BP, and PP as a fine aggregate with ratios of 5%, 10%, 15%, and 20% of sand in producing and assessing sustainable concrete. The static properties, i.e., compressive, tensile, flexural strength, and dynamic properties using the drop-weight impact test, were evaluated of such materials. The results showed that using IP as a partial replacement enhances both static and dynamic properties of concrete; the enhancement kept increasing up to 20% of IP, and the compressive, tensile, flexural strength, and impact energy increased by 8.4%, 12.5%, 8.5, and 125%, respectively. Therefore, IP can be suggested to replace sand by up to 20%. Using PP up to 15% enhanced the impact energy at failure by about 225%. It also observed that the optimum value for GP and BP was 10%. When using 10% GP the increase in the compressive, tensile, flexural strength, and impact energy was 11.7%, 25%, 21.5%, and 100%, respectively, while it increased by 12.9%, 7.6%, 15.4%, and 63% respectively when using BP.